Inventarisasi dan Identifikasi Lebah pada Terung (Solanum melongena L.) di Kabupaten Ogan Ilir, Sumatera Selatan - Saripudin, Saripudin; Firmanto, Riko; Riana, Nanda; Anggraini, Tria; Arisandi, Faisal; Mariana, Ivana Septa; Umayah, Abu; Gunawan, Bambang; Arsi, Arsi (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2022)
Saripudin S, Firmanto R, Riana N, Anggraini T, Arisandi F, Mariana IS, Umayah A, Gunawan B, Arsi A. 2022. Inventory and identification of bees on eggplant (Solanum melongena L.) in Ogan Ilir Regency, South Sumatra. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-10 Tahun 2022, Palembang 27 Oktober 2022. pp. 480-488. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Eggplant (Solanum melongena L.) is one of the vegetable commodities with high economic value. One of the factors that affect the increase in crop yields is the presence of bees as pollinating insects. The purpose of this study was to identify bee species found in eggplant in Ogan Ilir Regency, South Sumatra. The sampling method used in this research is purposive sampling method. Sampling methods include direct observation and hand picking. Observations and sampling were carried out 3 times in the villages of Tanjung Pering, Permata Baru, Palem Raya, and Timbangan, Ogan Ilir Regency, South Sumatra. The results of the observations showed that there were two species of stinging bees, Apis cerana and Nomia sp. Apis cerana has a black body, the clipeus on the head is black covered with brown hair. The thorax is black and covered with brownish-yellow hair. The propodeum (first abdominal segment) is brownish yellow. The third to the last segment of the abdomen is black. Nomia sp. has a black body measuring 12 mm. Clipeus on the black head there is brownish white hair. The thorax is black and covered with brownish-yellow hairs. The hind limbs are brown covered in brownish white hair. There is a green band on the belly. So, the bee species found in eggplant plants in Ogan Ilir Regency are Apis cerana and Nomia sp. Suggestions for research development can be by observing more than 2 eggplant varieties.